On the discrete algorithm of maximum velocity curve about halfpipe - Jiang, Y.; Liu, C.; Ye, Y.; Li, J.; Dong, Y. (24th Chinese Control and Decision Conference (CCDC), 2012)
In this study, we consider some discrete method of Euler-Lagrange differential equation to solve the maximum descend velocity problem. This method was derived from the solving of brachistochrone problem. Considering the effect of the friction and centripetal force to the maximum velocity, we give an energy model defined by an integral form. According to conservation law of energy, using finite element method we make an iterative formula to approximate the maximum velocity.